2023
DOI: 10.3390/pr11092702
|View full text |Cite
|
Sign up to set email alerts
|

Exergy Loss Assessment Method for CNC Milling System Considering the Energy Consumption of the Operator

Zhaohui Feng,
Hua Zhang,
Wei Li
et al.

Abstract: Modeling and assessing the sustainability of machining systems has been considered to be a crucial approach to improving the environmental performance of machining processes. As the most common machining system, the computer numerical control (CNC) milling system is a typical man–machine cooperative system where the activities of the machine tool and operator generate material and energy consumption. However, the energy consumption of the operator in the CNC milling system has often been ignored in most existi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Furthermore, the proportion of time spent on the tool setting process while machining a workpiece is considerable, which means that large amounts of electrical energy are consumed in the tool setting process. In one of our previous studies [47], we found that in a machining experiment, the proportions of time and electrical energy consumed in the tool setting process were 33.84% and 21.60%, respectively. Nevertheless, on the one hand, most of the previous studies on the tool setting process have focused on the principles and new methods [31,35], accuracy control and enhancement [34], and operation efficiency [32], among other topics.…”
Section: Discussionmentioning
confidence: 79%
“…Furthermore, the proportion of time spent on the tool setting process while machining a workpiece is considerable, which means that large amounts of electrical energy are consumed in the tool setting process. In one of our previous studies [47], we found that in a machining experiment, the proportions of time and electrical energy consumed in the tool setting process were 33.84% and 21.60%, respectively. Nevertheless, on the one hand, most of the previous studies on the tool setting process have focused on the principles and new methods [31,35], accuracy control and enhancement [34], and operation efficiency [32], among other topics.…”
Section: Discussionmentioning
confidence: 79%